Histopathology of balloon‐dilation eustachian tuboplasty. (22nd August 2014) - Kivekäs, Ilkka; Chao, Wei‐Chieh; Faquin, William; Hollowell, Monica; Silvola, Juha; Rasooly, Tali; Poe, Dennis
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Surgical intervention of the Eustachian tube (ET) has become increasingly common in the past decade, and balloon dilation has shown promising results in recent studies. It is unclear how balloon dilation enhances ET function. Our aim was to evaluate histological changes in the ET's mucosal lumen comparing before balloon dilation, immediately after, and postoperatively. Study Design Case series. Methods Thirteen patients with bilateral ET dysfunction were enrolled. Biopsies of the ET mucosa were obtained just before balloon dilation; immediately after; and in three cases, 5 to 12 weeks postoperatively. Specimens were retrospectively examined under light microscopy by two pathologists blinded to the clinical information and whether specimens were pre‐ or postballoon dilation. Results Preoperative biopsies were characterized by inflammatory changes within the epithelium and submucosal layer. Immediate response to balloon dilation was thinning of the mucosa, shearing of epithelium and crush injury to the submucosa, especially to lymphocytic infiltrates. Postoperative biopsies demonstrated healthy pseudocolumnar epithelium and replacement of lymphocytic infiltrate with a thinner layer of fibrous tissue. Conclusion Reduction of inflammatory epithelial changes and submucosal inflammatory infiltrate appeared to be the principal result of balloon dilation. The balloon may shear or crush portions of inflamed epithelium but usually spared the basal layer, allowing for rapid healing. Additionally, it appeared to effectively crush lymphocytes and lymphocytic follicles that may become replaced with thinner fibrous scar. Histopathology of the ET undergoing balloon dilation demonstrated effects that could reduce the overall inflammatory burden and may contribute to clinical improvement in ET function. Level of Evidence 4. Laryngoscope, 125:436–441, 2015